2007
DOI: 10.1590/s0102-86502007000500007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intrathecal administration of betamethasone over the dogs' spinal cord and meninges

Abstract: Purpose:To determinate the potential clinical and histological changes due the injection of betamethasone, when administered into the canine intrathecal space. Methods: Twenty one animals were included in a random and blind manner in the study. After general anesthesia, intrathecal puncture was performed and 1 ml of the random solution was injected. The G1 dogs received 0.9% saline solution, the G2 dogs received 1.75 mg betamethasone and the G3 dogs received 3.5 mg of betamethasone. The animals were clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…intrathecal but not epidural, administration of methylprednisolone and betamethasone at high doses and continuously showed dosedependent intrathecal inflammatory reactions in dogs [25][26][27] . However, neuronal injuries, demyelination, or gliosis were not clinically observed in any animal in these studies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…intrathecal but not epidural, administration of methylprednisolone and betamethasone at high doses and continuously showed dosedependent intrathecal inflammatory reactions in dogs [25][26][27] . However, neuronal injuries, demyelination, or gliosis were not clinically observed in any animal in these studies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It can lead to the development of hypotension, migration of local anesthetic towards the cranial area, and respiratory depression due to blockage of the diaphragm and intercostal muscles, possibly resulting in death. Therefore, the choice of local anesthesia for spinal or IT anesthesia is critical [1][2][3][6][7][8][9] . There are many studies where the advantages of bupivacaine and ropivacaine are demonstrated [1,2,16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Five minutes later, dogs were placed in the prone position. IT anesthesia was performed under aseptic conditions with either 20 mg [1] (4 mL as total dose) bupivacaine (Marcaine®, 5 mg/mL Astra Zenaca) or 30 mg [1] (4 mL as total dose) ropivacaine (Naropin® 7.5 mg/mL, Astra Zenaca) injected into the L7-S1 or L6-L7 as previously described [1,3,5,7,8] . If the spinal puncture was suspicious or unsuccessful, it was not insisted and abandoned.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations